An in-depth analysis of a piece of shit: distribution of Schistosoma mansoni and hookworm eggs in human stool. - Stefanie J Krauth; Jean T Coulibaly; Stefanie Knopp; Mahamadou Traoré; Eliézer K N'Goran; Jürg Utzinger (PLoS Neglected Tropical Diseases)
Background An accurate diagnosis of helminth infection is important to improve patient management. However, there is considerable intra- and inter-specimen variation of helminth egg counts in human feces. Homogenization of stool samples has been suggested to improve diagnostic accuracy, but there are no detailed investigations. Rapid disintegration of hookworm eggs constitutes another problem in epidemiological surveys. We studied the spatial distribution of Schistosoma mansoni and hookworm eggs in stool samples, the effect of homogenization, and determined egg counts over time in stool samples stored under different conditions. Methodology Whole-stool samples were collected from 222 individuals in a rural part of south Côte d'Ivoire. Samples were cut into four pieces and helminth egg locations from the front to the back and from the center to the surface were analyzed. Some samples were homogenized and fecal egg counts (FECs) compared before and after homogenization. The effect of stool storing methods on FECs was investigated over time, comparing stool storage on ice, covering stool samples with a water-soaked tissue, or keeping stool samples in the shade. Principal findings We found no clear spatial pattern of S. mansoni and hookworm eggs in fecal samples. Homogenization decreased S. mansoni FECs (p = 0.026), while no effect was observed for hookworm and other soil-transmitted helminths. Hookworm FECs decreased over time. Storing stool samples on ice or covered with a moist tissue slowed down hookworm egg decay (p<0.005). Conclusions/significance Our findings have important implications for helminth diagnosis at the individual patient level and for epidemiological surveys, anthelmintic drug efficacy studies and monitoring of control programs. Specifically, homogenization of fecal samples is recommended for an accurate detection of S. mansoni eggs, while keeping collected stool samples cool and moist delayed the disintegration of hookworm eggs.